Serum thyroid-stimulating hormone receptor antibody levels and thyroid dysfunction after hysterosalpingography: a case-control study. (3rd October 2021) - So, Shuhei; Hashimoto, Koshi; Mori, Masatomo; Endo, Shigeki; Yamaguchi, Wakasa; Miyano, Naomi; Murabayashi, Nao; Tawara, Fumiko
Abstract: Objective: Hysterosalpingography (HSG) performed with an iodine contrast media can cause thyroid dysfunction, including thyrotoxicosis and hypothyroidism. We investigated the association between the serum levels of thyroid-stimulating hormone receptor antibody (TRAb), an indicator of Graves' disease, and abnormal thyroid function after performing HSG. Methods: The screening of TRAb was conducted in 362 patients who first visited the Tawara IVF Clinic between April and September 2018. The association between TRAb levels and the effects of HSG examinations on thyroid function were evaluated. Results: Of the 362 patients, 2 (0.55%) had high levels (>2.0 IU/L) of TRAb, whereas 18 (5.0%) had intermediate TRAb levels, ranging from 0.3 to 1.9 IU/L. Of the 98 women (including 7 of the 18 women with TRAb level 0.3–1.9 IU/L, and 91 of the 342 women with TRAb level <0.3 IU/L) who had undergone HSG, two women developed overt thyrotoxicosis after HSG, and the frequency was significantly higher ( p  = .0044) in the group with intermediate levels of TRAb (28.6%, 2 of 7) than that in the group with low TRAb levels (<0.3 IU/L; 0.0%, 0 of 91). Conclusions: These findings indicate that increased serum levels of TRAb are significantly associated with the development of thyrotoxicosis after HSG.